Nrf2–ARE Signaling Acts as Master Pathway for the Cellular Antioxidant Activity of Fisetin - Huihui Zhang; Wan Zheng; Xiangling Feng; Fei Yang; Hong Qin; Shusong Wu; De-Xing Hou; Jihua Chen (Molecules, 2019)
Fisetin, a dietary flavonoid, is reported to have cellular antioxidant activity with an unclear mechanism. In this study, we investigated the effect of fisetin on the nuclear factor, erythroid 2-like 2 (Nrf2) signaling pathway in HepG2 cells to explore the cellular antioxidant mechanism. Fisetin upregulated the mRNA expression of heme oxygenase-1 (HO-1), glutamate-cysteine ligase catalytic subunit (GCLC), glutamate-cysteine ligase modifier subunit (GCLM), and NAD(P)H quinone oxidoreductase-1 (NQO1), and induced the protein of HO-1 but had no significant effect on the protein of GCLC, GCLM and NQO1. Moreover, nuclear accumulation of Nrf2 was clearly observed by immunofluorescence analysis and western blotting after fisetin treatment, and an enhanced luciferase activity of antioxidant response element (ARE)-regulated transactivation was obtained by dual-luciferase reporter gene assays. In addition, fisetin upregulated the protein level of Nrf2 and downregulated the protein level of Kelch-like ECH-associated protein 1 (Keap1). However, fisetin had no significant effect on Nrf2 mRNA expression. When protein synthesis was inhibited with cycloheximide (CHX), fisetin prolonged the half-life of Nrf2 from 15 min to 45 min. When blocking Nrf2 degradation with proteasome inhibitor MG132, ubiquitinated proteins were enhanced, and fisetin reduced ubiquitination of Nrf2. Taken together, fisetin translocated Nrf2 into the nucleus and upregulated the expression of downstream HO-1 gene by inhibiting the degradation of Nrf2 at the post-transcriptional level. These data provide the molecular mechanism to understand the cellular antioxidant activity of fisetin.